A Review of Telmisartan in the Treatment of Hypertension: Blood Pressure Control in the Early Morning Hours - Gosse, Philippe (Dove Medical Press, 2006)
Measurement of blood pressure in the clinic may provide a false impression of blood pressure control. Ambulatory blood pressure monitoring (ABPM) allows the automatic recording of the circadian variation in blood pressure and evaluation of the efficacy of antihypertensive medication throughout the dosing interval. Ambulatory blood pressure provides more effective prediction of cardiovascular risk; blood pressure control at the time of heightened risk in the early morning after waking and before taking the next dose of medication is becoming important in order to improve long-term prognosis. To achieve blood pressure control in the early morning, a long-acting antihypertensive agent is essential. Telmisartan, an angiotensin II receptor blocker, as well as having a terminal elimination halflife of 24 h, has a large volume of distribution due to its high lipophilicity. The efficacy of telmisartan 80 mg monotherapy has been demonstrated using ABPM, with superior reduction in mean values for the last 6 h of the dosing interval compared with ramipril 10 mg and valsartan 80 mg. In addition, telmisartan 80 mg provides superior blood pressure control after a missed dose compared with valsartan 160 mg. When combined with hydrochlorothiazide (HCTZ) 12.5 mg, telmisartan 40 mg and 80 mg is more effective than losartan/HCTZ (50/12.5 mg) at the end of the dosing interval. Furthermore, greater reductions in last 6 h mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) are achieved with telmisartan/HCTZ (80/12.5 mg) than with valsartan/HCTZ (160/12.5 mg) in obese patients with type 2 diabetes and hypertension. Recent data from a large group of patients show that telmisartan 80 mg controls the early morning blood pressure surge more effectively than ramipril 5–10 mg and, thus, may have a greater beneficial effect on long-term cardiovascular risk. This supposition is being tested in the ONgoing Telmisartan Alone and in combination with Ramipril Global Endpoint Trial (ONTARGET) programme